New Trends in Parameter Identification for Mathematical Models (Trends in Mathematics,, 2018)
The Proceedings volume contains 16 contributions to the IMPA conference "New Trends in Parameter Identification for Mathematical Models", Rio de Janeiro, Oct 30 - Nov 3, 2017, integrating the "Chemnitz Symposium on Inverse Problems on Tour". This conference is part of the "Thematic Program on Parameter Identification in Mathematical Models" organized at IMPA in October and November 2017. One goal is to foster the scientific collaboration between mathematicians and engineers from the Brazialian, European and Asian communities. Main topics are iterative and variational regularization methods in Hilbert and Banach spaces for the stable approximate solution of ill-posed inverse problems, novel methods for parameter identification in partial differential equations, problems of tomography , solution of coupled conduction-radiation problems at high temperatures, and the statistical solution of inverse problems with applications in physics.